2018
DOI: 10.1128/aem.01166-18
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Response of a Metabolically Flexible Anoxygenic Phototroph to Fe(II) Oxidation

Abstract: The oxidation of Fe(II) by anoxygenic photosynthetic bacteria was likely a key contributor to Earth's biosphere prior to the evolution of oxygenic photosynthesis and is still found in a diverse range of modern environments. All known phototrophic Fe(II) oxidizers can utilize a wide range of substrates, thus making them very metabolically flexible. However, the underlying adaptations required to oxidize Fe(II), a potential stressor, are not completely understood. We used a combination of quantitative proteomics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Expression of pioABC is a poor marker for anoxygenic phototrophic Fe(II) oxidation in the environment since expression of pioABC occurs under photoheterotrophic conditions and photoautotrophic conditions with H2 and thiosulfate (36,49). It was proposed that pioABC expression could be a marker for photoautotrophic conditions since high levels of expression were only observed under photoautotrophic conditions when compared to photoheterotrophic growth with acetate (49). However, we found that expression of pioABC under photoheterotrophic conditions is dependent on the oxidation state of the carbon source provided and whether cells are carrying out nitrogen fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of pioABC is a poor marker for anoxygenic phototrophic Fe(II) oxidation in the environment since expression of pioABC occurs under photoheterotrophic conditions and photoautotrophic conditions with H2 and thiosulfate (36,49). It was proposed that pioABC expression could be a marker for photoautotrophic conditions since high levels of expression were only observed under photoautotrophic conditions when compared to photoheterotrophic growth with acetate (49). However, we found that expression of pioABC under photoheterotrophic conditions is dependent on the oxidation state of the carbon source provided and whether cells are carrying out nitrogen fixation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the combination of soft biological material with hard minerals brings unique challenges to imaging these interactions at nanoscale resolution. Traditionally, scanning electron or transmission electron microscopy techniques have been applied to great effect to study many aspects of microbe-mineral interactions, such as the formation of intra-or extracellular mineral precipitates, or intracellular organelles associated with energy gain or electron transfer [92]. However, over recent years, the number of articles related to geomicrobiology and containing HIM data has increased.…”
Section: Geomicrobiologymentioning
confidence: 99%